Changes in bone mass during the perimenopausal transition in naturally menopausal cynomolgus monkeys. Issue 1 (January 2016) - Kittivanichkul, Donlaporn; Watanabe, Gen; Nagaoka, Kentaro; Malaivijitnond, Suchinda
Abstract: Objective: This study measured the differences in bone mineral density and content in relation to changes in serum hormone and bone marker levels during the perimenopausal transition in naturally menopausal cynomolgus monkeys. Methods: The bone mineral density and content of premenopausal, perimenopausal, and early (0-< 5 y), mid (5-10 y), and late (> 10 y) postmenopausal monkeys were measured at the distal radius and proximal tibia in both metaphysis and diaphysis. Hormonal and bone marker levels were also measured. Results: The serum 17β-estradiol level significantly decreased during late postmenopause, whereas the serum follicle-stimulating hormone levels significantly increased from early postmenopause before declining at late postmenopause. Trabecular bone loss at metaphysis occurred once the animals entered into the perimenopausal period, whereas cortical bone loss gradually and continuously decreased, dependent on the time-course after perimenopause, and was greatest in the late postmenopausal period. Serum bone-specific alkaline phosphatase and urinary N-telopeptide of bone type-1 collagen levels were negatively correlated with the trabecular bone mineral content at metaphysis, whereas serum osteocalcin levels showed a negative correlation with the cortical bone mineral density at the diaphysis. The only positive linear correlation observed was between serum follicle-stimulating hormone and urinary N-telopeptide of bone type-1 collagen levels. Conclusions: Unlike the ovariectomized monkey models that do not retain the perimenopausal transition, naturally menopausal monkeys elicit different patterns of bone loss during the transition—an abrupt decline in the trabecular metaphysis and a gradual decline in the cortical diaphysis. Naturally menopausal cynomolgus monkeys offer an alternative model for osteoporosis research for postmenopausal women.